Penerapan Knowledge Management dan Pengembangan Sumber Daya Manusia Terhadap Produktivitas Karyawan di Perum BULOG - Vitratin, Vitratin; Yuniastuti, Rina Milyati; Eliyana, Rahmi; Ariyanto, Pandu (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2024)
The aim of the research is to examine the effect of knowledge management and human resource development on employee productivity at the Lampung Regional Office Logistics Agency Public Company. The quantitative research method used in this research. The sample was employees at the Perum BULOG with a sample of 53 respondents. The T-test for the Knowledge Management variable has no effect on employee productivity at the Public Company of the Lampung Regional Office Logistics Affairs Agency, this means that for employee productivity other things are needed that the researchers did not examine. Human Resource Development has an influence on Employee Productivity at Public Companies, Logistics Affairs Agency, Lampung Regional Office. This means that employees need higher character development. In the F test, it is known that each of the independent variables Knowledge Management and Human Resource Development has an effect on Employee Productivity at the Public Company of the Lampung Regional Office Logistics Affairs Agency because the calculated f value is greater than f table. Meanwhile, the R Test shows that knowledge management and human resource development only have an effect of 12.2% on Employee Productivity of Public Company Logistics Affairs Agency, Lampung Regional Office. It is hoped that future researchers will add complete variables to employee productivity performance.